2020
DOI: 10.1111/gtc.12741
|View full text |Cite
|
Sign up to set email alerts
|

RBM10 regulates centriole duplication in HepG2 cells by ectopically assembling PLK4‐STIL complexes in the nucleus

Abstract: RNA‐binding motif protein 10 (RBM10) primarily regulates alternative splicing of certain genes. Loss‐of‐function mutations in RBM10 have been frequently reported in patients with various cancers. However, how RBM10 levels affect cell proliferation and tumorigenesis remains unknown. To elucidate the role of RBM10 in cell proliferation, we established HepG2‐RBM10 knockout cell lines and derivative doxycycline‐inducible RBM10‐expressing cells. RBM10 over‐expression caused growth arrest in the M phase with a monop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Numerous RNAi-based screens have revealed splicing factors that directly contribute to open mitosis. For example, the RBM10 protein regulates centriole duplication and its overexpression in tumor cells leads to cell cycle arrest in the M phase and the formation of a monopolar spindle due to disturbances in centriole duplication [80]. According to Pellacani and co-authors, splicing factors SF3A2 and PRP31 are necessary for normal chromosome segregation, as they regulate the interaction between kinetochores, spindle microtubules, and the essential kinetochore complex Ndc80 [81].…”
Section: Cell Cycle Progressionmentioning
confidence: 99%
“…Numerous RNAi-based screens have revealed splicing factors that directly contribute to open mitosis. For example, the RBM10 protein regulates centriole duplication and its overexpression in tumor cells leads to cell cycle arrest in the M phase and the formation of a monopolar spindle due to disturbances in centriole duplication [80]. According to Pellacani and co-authors, splicing factors SF3A2 and PRP31 are necessary for normal chromosome segregation, as they regulate the interaction between kinetochores, spindle microtubules, and the essential kinetochore complex Ndc80 [81].…”
Section: Cell Cycle Progressionmentioning
confidence: 99%
“…In contrast, RBM10 knockdown increases the cytoplasmic PLK4 levels and causes abnormal cells with more than 4 centrioles in HepG2 cells, but not in A549 cells. This is an example to indicate that the cellular levels of RBM10 should be securely controlled ( Kunimoto et al, 2020 ). Guan et al also reported cell cycle arrest due to overexpressed RBM10 in the G0/G1 phase in A549 cells and in the S phase in H1299 cells ( Guan et al, 2017 ).…”
Section: Functions Of Rbm10mentioning
confidence: 99%
“…In the AS reaction, RBM10 promotes the exclusion of cassette exons from target pre-mRNAs, and less frequently, other AS events ( Wang et al, 2013 ; Bechara et al, 2013 ; Zheng et al, 2013 ; Inoue et al, 2014 ). It is also involved in reactions other than AS, such as 3′ end processing of some pre-mRNAs ( Mueller et al, 2009 ; Mohan et al, 2018 ), p53 stabilization ( Jung et al, 2020 ), cell cycle arrest ( Guan et al, 2017 ; Kunimoto et al, 2020 ), and anti-viral reactions ( Pozzi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, platinum-based chemotherapy was used for the treatment of lung adenocarcinoma, but due to the insensitivity of lung adenocarcinoma to chemotherapy and the generation of drug resistance, the therapeutic effect was not sufficient [35]. With the exploration of genomics and molecular biology, researchers have made new discoveries on the formation, invasion, and migration mechanisms of lung adenocarcinoma and re-examined the treatment of nonsmall-cell lung cancer [36]. In recent years, RNA-binding proteins (RBM) have gradually come into the research field, among which RBM10 and RBM5 can regulate apoptosis-related genes [37].…”
Section: Discussionmentioning
confidence: 99%